Capital Structure and Financial Performance : A Study of Indian Cement Companies - Dr. Umed Singh (Innovative Research Thoughts, 2023)
The capital structure decision is the most crucial decision for firms/companies because it affects the profitability and risk of firms and shareholders. The present study examines the relationship of capital structure with the financial performance of BSE listed cement companies in India. For achieving the objective of the study, five BSE listed companies of Indian cement industry were taken into sample by using judgemental sampling. Under this study, secondary data relating to capital structure and financial performance were gathered from the annual reports of sampled companies for a period of ten years from 2009-10 to 2018-19. The descriptive statistical tools-average, standard deviation, coefficient of variance, skewness, kurtosis and correlation analysis were applied for analysing the data. The obtained results of this study explicated that capital structure variable-debt-equity ratio has negative relationship with financial performance variables-net profit, operating profit, return on assets, return on capital employed, return on equity and earnings per share in BSE listed companies of Indian cement industry.